2012
DOI: 10.1177/016264341202700303
|View full text |Cite
|
Sign up to set email alerts
|

Online Instruction for K-12 Special Education: A Review of the Empirical Literature

Abstract: Gates Foundation ProjectOnline environments increasingly are becoming a part of our schools. While online education holds tremendous promise-offering viable and attractive options for advancing student skills, increasing access, and potentially lowering the cost of educational services-there is little research on the efficacy of online instruction for students with disabilities. A comprehensive review of the literature was conducted to determine if the existing literature can provide a research base for delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…Online classrooms -support many types of learners, including students who qualify for special education services, English language learners (ELLs), students who receive free and reduced-price lunch, students from varied ethnic backgrounds, and other diverse students‖ (Coy, 2014). Many parents of students with special needs are attracted to fully online opportunities, due to the individualized programs and broader selection of classes (Marteney & Bernadowski, 2016;Vasquez & Straub, 2012). The opportunity for the student with learning disabilities to -work at their own pace,‖ within a supportive and nurturing environment, provides a sense of protection from the -social and behavioral challenges of brick-and-mortar schools‖ (Coy, 2014).…”
Section: The Online Learning Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Online classrooms -support many types of learners, including students who qualify for special education services, English language learners (ELLs), students who receive free and reduced-price lunch, students from varied ethnic backgrounds, and other diverse students‖ (Coy, 2014). Many parents of students with special needs are attracted to fully online opportunities, due to the individualized programs and broader selection of classes (Marteney & Bernadowski, 2016;Vasquez & Straub, 2012). The opportunity for the student with learning disabilities to -work at their own pace,‖ within a supportive and nurturing environment, provides a sense of protection from the -social and behavioral challenges of brick-and-mortar schools‖ (Coy, 2014).…”
Section: The Online Learning Environmentmentioning
confidence: 99%
“…Online supplemental learning is becoming a viable option for special educators, as the schools implement advanced technology into classrooms and learning labs. According to Vasquez and Straub (2012), online activities, coinciding with traditional instruction, -Meet the needs of students with disabilities because of their ability to accommodate students with extended time and varied multimedia technologies‖ (p. 32). Though more time consuming to prepare than the traditional lesson plan, integrating online resources has demonstrated success in learning gains with students of special needs and learning disabilities (Smith & Basham, 2014).…”
Section: Online Resourcesmentioning
confidence: 99%
“…Means et al highlighted the need for more research, referring to the collection as ''a very small number of studies, especially considering the extent to which secondary schools are using online courses and the rapid growth of online instruction in K-12 education as a whole'' (p. 54). More recently, Vasquez and Straub (2012) conducted a systematic review of literature related to OWI restricting their search to academic outcomes of struggling writers, including search terms to capture studies relating to students with disabilities; only three studies with academic outcomes were identified.…”
Section: Writing Instruction Online For Students With Ldmentioning
confidence: 99%
“…Archambault and Crippen (2009) report that one survey found that out of all K-12 students enrolled in online courses, 68 percent were at the high school level, 29 percent were in ungraded or combined schools, 2 percent were junior high or middle school students, and 1 percent were at the elementary level. Although the term online courses implies that students take these courses outside of school, one survey showed that most students (86%) access the Online Instruction and Virtual Schools 73 resources for these courses at their school (Vasquez and Straub 2012). Schools can implement online distance education in various ways.…”
Section: Definition Of Online Courses and Virtual Schoolsmentioning
confidence: 99%
“…Students with disabilities, for example, benefit from this format as a result of the individualized instruction it creates, allowing them extended time, the use of a variety of multimedia technologies, and flexible location (Vasquez and Straub 2012). For students with disabilities who cannot attend traditional schools, the flexibility in location is crucial, and for students with learning disabilities, varied multimedia technology is beneficial for developing literacy (Vasquez and Straub 2012).…”
Section: Theories For Using Online Instructionmentioning
confidence: 99%